2020
DOI: 10.1111/cts.12817
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomic Profiles Associated With Untreated Metabolic Syndrome Patients in the Chinese Population

Abstract: Metabolomics is a promising technology for elucidating the mechanisms of metabolic syndrome (MetS). However, measurements in patients with MetS under different conditions vary. Metabolomics experiments in different populations and pathophysiological conditions are, therefore, indispensable. We performed a serum metabolomics investigation in untreated patients with MetS in the Chinese population. Untreated patients with MetS were recruited to this study. Metabolites were measured using a traditional 1H nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
(70 reference statements)
3
4
0
Order By: Relevance
“…In addition, glutamine was shown to be upregulated in the normoglycemic MetS group relative to that in the control group (3.5-fold), emphasizing its association with MetS (Table 2). Li Y et al reported several pathways to be associated with MetS; however, in accordance with our results, D-glutamine and D-glutamate metabolism was impacted [33]. In our results, D-glutamine and D-glutamate metabolism was highly affected by L-glutamine and L-glutamate (L-glutamic acid) metabolites, which tended to be upregulated as reported above.…”
Section: The D-glutamine and D-glutamate Metabolism Pathwaysupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, glutamine was shown to be upregulated in the normoglycemic MetS group relative to that in the control group (3.5-fold), emphasizing its association with MetS (Table 2). Li Y et al reported several pathways to be associated with MetS; however, in accordance with our results, D-glutamine and D-glutamate metabolism was impacted [33]. In our results, D-glutamine and D-glutamate metabolism was highly affected by L-glutamine and L-glutamate (L-glutamic acid) metabolites, which tended to be upregulated as reported above.…”
Section: The D-glutamine and D-glutamate Metabolism Pathwaysupporting
confidence: 92%
“…Phenylalanine metabolism was impacted when comparing the normoglycemic MetS group with the control group (Figure 5A). Li Y et al also observed phenylalanine metabolism to be associated with MetS [33]. Our data showed that phenylalanine metabolism was altered due to phenylacetaldehyde and hippurate both being upregulated in the normoglycemic MetS group (1.26-fold and 144.6-fold, respectively).…”
Section: The Phenylalanine Metabolism Pathwaysupporting
confidence: 67%
“… 5 Metabolic syndrome represents a cluster of metabolic derangements, and emerging technologies have remarkably enhanced the comprehensive elucidation of its relevant mechanisms by revealing variations in diverse metabolites at specific disease stages. 6 , 7 In addition, numerous studies have shown an association between metabolic syndrome and various cancers. 8 Importantly, due to its aggressive involvement in multiple malignancies, metabolic syndrome has been shown to serve as a prognostic indicator in various cancers, including breast cancer, 9 gastric cancer, 10 colorectal cancer, 11 , 12 oesophageal squamous cell carcinoma, 13 prostate cancer, 14 ovarian cancer, 15 renal cancer, 16 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we performed a 1 H NMR study to explore the metabolic characteristics of untreated patients with MetS. We found that such untreated patients have peculiar metabolic characteristics, such as ketosis tendency, early kidney damage, activation of oxidative signaling, and inflammatory response, which suggested that the pathophysiological state might worsen if MetS is left untreated (11). The metabolomics approach is also used for metabolomic profile elucidation in obesity.…”
Section: Introductionmentioning
confidence: 99%